Polymer conversion wave-absorbing ceramic constructed by crosslinking strategy as well as preparation method and application of polymer conversion wave-absorbing ceramic

By introducing a cross-linking reaction between alkynyl-containing poly(diacetylene)dimethylsilane and hyperbranched polyborosilazane into the polymer precursor, SiBCN ceramics with excellent electromagnetic wave absorption performance were prepared, which solved the problem of uneven material dispersion and achieved a more stable electromagnetic wave absorption effect.

CN119841645AActive Publication Date: 2025-04-18CHANGAN UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510070790.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

In the prior art, when preparing electromagnetic wave absorbing materials, the material is unevenly dispersed, resulting in unstable electromagnetic wave absorbing performance.

Method used

By regulating the molecular structure of the polymer precursor, the alkynyl-containing poly(diacetylene)dimethylsilane is used to crosslink with hyperbranched polyborosilazane to construct a new polymer precursor, and wave absorbing ceramics are prepared by high-temperature pyrolysis.

Benefits of technology

The conversion of carbon elements inside the ceramic material into an ordered carbon structure is achieved, and nanowires and silicon carbide nanocrystals are generated, which significantly improves the electromagnetic wave absorption performance of the material, and makes the material components evenly disperse and have better stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841645A_ABST
    Figure CN119841645A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer conversion wave-absorbing ceramic constructed by a cross-linking strategy, and a preparation method and application thereof, belongs to the technical field of ceramics, and solves the problem of non-uniform material dispersion caused by a preparation method in the prior art. The method comprises the following steps: uniformly dissolving a hyperbranched polyborosilazane precursor containing a silicon-hydrogen bond and poly (diacetylene) dimethylsilane containing alkynyl in anhydrous tetrahydrofuran according to a mass ratio of (5-20): 1, adding a catalyst platinum (0)-1, 3-diethylene-1, 1, 3, 3-tetramethyldisiloxane, reacting at 45-60 DEG C overnight, removing anhydrous tetrahydrofuran, and carrying out vacuum drying to obtain the hyperbranched polyborosilazane polymer. A polymer precursor is obtained; and thermally crosslinking the polymer precursor at 400 DEG C, grinding into powder, pressing into a blank, and pyrolyzing at 1400 DEG C to obtain the polymer converted wave-absorbing ceramic. According to the preparation method provided by the invention, two kinds of polysilane are uniformly mixed and cross-linked from a molecular level to obtain a new polymer precursor, and the wave-absorbing ceramic with uniformly dispersed structural components is prepared through high-temperature pyrolysis, so that a more stable effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic technology, and more specifically to a polymer-converted microwave-absorbing ceramic constructed by a cross-linking strategy, and a preparation method and application thereof. Background Art

[0002] With the rapid development of wireless communication technology, radar, satellite communication and other fields, electromagnetic wave pollution has gradually become an important problem in daily life. Electromagnetic waves not only interfere with electronic equipment and communication systems, but also pose a potential threat to human health. Especially in the stealth field of aerospace, military and other fields, equipment and systems in high temperature environments have put forward more stringent requirements on the performance of electromagnetic wave absorbing materials. Therefore, the development of electromagnetic wave absorbing materials with good stability and high performance has become an urgent task to meet the needs of modern industry.

[0003] Polymer-derived Ceramics (PDCs) are a type of ceramic material prepared by high-temperature pyrolysis of polymer precursors. Under high-temperature conditions, PDCs exhibit excellent thermal stability and structural integrity, and are an important method for preparing ceramic-based absorbing materials. In recent years, a series of research results on PDCs absorbing materials have been achieved, including PDC-SiC, SiCN, SiCNO, SiOC, and SiBCN. Among them, PDC-SiBCN ceramics, due to their unique elemental composition, exhibit superior high-temperature stability (up to 1600°C), excellent oxidation resistance, and chemical stability. Therefore, the application prospects of PDCs-SiBCN absorbing ceramics in military stealth technology are particularly prominent.

[0004] At present, there have been studies on directly introducing materials such as carbon nanotubes, graphene oxide, and carbon nanowires into polymer precursors, or doping metals into precursors to improve the dielectric properties of ceramic materials, thereby enhancing their electromagnetic wave absorption capabilities. However, the use of doping and blending to adjust the electromagnetic wave absorption performance of materials not only requires a lot of time to blend materials, but also faces the problem of difficult uniform dispersion of ceramic components. Summary of the invention

[0005] The present invention provides a polymer-converted microwave-absorbing ceramic constructed by a cross-linking strategy and a preparation method and application thereof, so as to solve the problem of uneven material dispersion caused by the preparation method in the prior art.

[0006] In a first aspect, the present invention provides a method for preparing a polymer-converted absorbing ceramic, comprising the following steps: uniformly dissolving a hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds and an alkynyl-containing poly(diacetylene)dimethylsilane in anhydrous tetrahydrofuran at a mass ratio of 5 to 20:1, adding a catalyst platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane, reacting overnight at a temperature of 45 to 60°C, and then removing the anhydrous tetrahydrofuran to obtain a polymer precursor; thermally cross-linking the polymer precursor at 400°C, grinding it into powder, pressing it into a embryo body, and pyrolyzing it at 1400°C to obtain the polymer-converted absorbing ceramic.

[0007] As a possible implementation method, the preparation of the hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds includes the following steps: under ice bath conditions, a borane dimethyl sulfide complex and methylvinyldichlorosilane are mixed and added to a reaction container, and then reacted at room temperature to obtain a tri(dichlorosilylethyl)borane monomer; dichloromethylsilane and hexamethyldisilazane are added to the tri(dichlorosilylethyl)borane monomer, and the temperature is raised to 180° C. and reacted for 2 to 4 hours to obtain the hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds.

[0008] As a possible implementation manner, the molar ratio of the borane dimethyl sulfide complex, the methylvinyldichlorosilane, the dichloromethylsilane and the hexamethyldisilazane is 1:3:1:5.6; and / or, the reaction is carried out at room temperature for 48 hours.

[0009] As a possible implementation method, the preparation of the alkynyl-containing poly(diacetylene) dimethylsilane includes the following steps: adding n-butyl lithium and hexachloro-1,3-butadiene to anhydrous tetrahydrofuran at a temperature of -78°C under anaerobic conditions, and stirring for reaction; slowly adding dichlorodimethylsilane to maintain the reaction; adding a capping agent and performing purification treatment to obtain the alkynyl-containing poly(diacetylene) dimethylsilane.

[0010] As a possible implementation method, the purification treatment includes the steps of: after removing excess tetrahydrofuran in the reaction system by rotary evaporation, adding the reaction system dropwise into an anhydrous methanol solution for precipitation, filtering, and obtaining a crude product; after re-dissolving the crude product in tetrahydrofuran, adding anhydrous methanol for re-precipitation, filtering, repeating this step 1 to 3 times, and then vacuum drying to obtain the alkynyl-containing poly(diacetylene) dimethylsilane.

[0011] As a possible implementation, the molar ratio of the n-butyl lithium, the hexachloro-1,3-butadiene and the dichlorodimethylsilane is 4:1:1; and / or the stirring reaction time is 6 hours; and / or the reaction is maintained for 12 hours.

[0012] In a second aspect, the present invention provides a polymer-converted absorbing ceramic prepared by the preparation method described in any possible implementation of the first aspect.

[0013] In a third aspect, the present invention provides an application of the polymer-converted absorbing ceramic described in any possible implementation of the second aspect in the field of aerospace.

[0014] In view of the problems of the prior art, the present invention takes PDCs-SiBCN as the research object, and by regulating the molecular structure of the precursor, uses alkynyl-containing poly(diacetylene) dimethylsilane (PDSDA) and hyperbranched polyborosilazane (hb-PBSZ) to completely dissolve and then perform molecular cross-linking, construct a new polymer precursor and pyrolyze at high temperature to prepare absorbing ceramics. The carbon elements inside the polymer-converted SiBCN ceramic after PDSDA modification of hb-PBSZ are converted into an ordered carbon structure, and the in-situ generation of nanowires and silicon carbide nanocrystals is achieved, thereby giving the material excellent electromagnetic wave absorption performance; the technical solution of the present invention is to design the structure at the molecular level so that the polymer-converted ceramic components are evenly dispersed to achieve a more stable effect. In addition, by adjusting the content of PDSDA, the dielectric constant and absorbing performance of the material can be further adjusted.

[0015] The present invention introduces PDSDA containing an alkynyl structure in the main chain into hyperbranched polyborosilazane through molecular cross-linking, and pyrolyzes it at high temperature to prepare microwave-absorbing ceramics. It is shown that the addition of PDSDA helps to form structures such as ordered carbon, nanofibers and silicon carbide nanocrystals in ceramic microwave-absorbing materials. With the increase of the amount of PDSDA added, the silicon carbide crystallization of the ceramic is gradually enhanced and the proportion of ordered carbon increases. As a new type of electromagnetic wave absorbing material, hb-PBSZ@PDSDA ceramics have good electromagnetic wave absorption application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 Fourier transform infrared spectra (FT-IR) of hb-PBSZ, hb-PBSZ@PDSDA-20:1 precursor, hb-PBSZ@PDSDA-10:1 precursor, hb-PBSZ@PDSDA-5:1 precursor and PDSDA provided in the embodiments of the present invention.

[0018] Figure 2The hydrogen element nuclear magnetic resonance spectrum of the PDSDA in the deuterated chloroform solvent provided in the embodiment of the present invention.

[0019] Figure 3 The carbon element nuclear magnetic resonance spectrum of the deuterated chloroform solvent of PDSDA provided in an embodiment of the present invention.

[0020] Figure 4 The morphological characterization results of hb-PBSZ@PDSDA-10:1 provided in the embodiment of the present invention, wherein A is a scanning electron microscope image, B is a transmission electron microscope image, and C is an elemental energy spectrum image.

[0021] Figure 5 XRD analysis results of hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 provided in the embodiments of the present invention.

[0022] Figure 6 The Raman spectral analysis results of hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 provided in the embodiments of the present invention.

[0023] Figure 7 The reflection coefficient curve analysis results of hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] In order to solve the problem of uneven dispersion of material components caused by the preparation method in the prior art, the embodiment of the present invention provides a preparation and characterization experiment of a polymer-converted absorbing ceramic constructed by a cross-linking strategy.

[0026] The characterization results show that by regulating the molecular structure of the precursor, cross-linking poly(diacetylene) dimethylsilane (PDSDA) containing alkyne groups with hyperbranched polyborosilazane (hb-PBSZ) can promote the transformation of carbon elements inside the pyrolyzed SiBCN ceramic into an ordered carbon structure, and achieve in-situ generation of nanowires and silicon carbide nanocrystals, thus giving the material excellent electromagnetic wave absorption performance; the structure is designed from the inside of the molecule to make the polymer-converted ceramic structure components dispersed evenly, achieving a more stable effect. In addition, by adjusting the content of PDSDA, the dielectric constant and wave absorption performance of the material can be further adjusted.

[0027] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0028] Example 1

[0029] This example provides a preparation experiment of polymer-converted microwave-absorbing ceramics constructed by a cross-linking strategy.

[0030] The Schlenk glass bottle was treated with double-row tube technology to be anhydrous and oxygen-free. In an argon atmosphere, 50 mL of anhydrous tetrahydrofuran was injected into a 250 mL reaction bottle, and the reaction system was kept at -78 ° C by a liquid nitrogen acetone bath. N-butyl lithium (0.1257 mol) and hexachloro-1,3-butadiene (0.0314 mol) were slowly added and reacted for 6 hours under magnetic stirring. Subsequently, at the same temperature, 0.0314 mol of dichlorodimethylsilane was slowly added and the reaction was maintained for 12 hours. Finally, 2 mL of trimethylchlorosilane was added as a capping agent to cap the reaction system to obtain a dark brown liquid, and the experiment was completed. During the product purification process, the excess tetrahydrofuran is first removed by rotary evaporation, and then dropped into an excess of anhydrous methanol solution for precipitation, and a crude PDSDA product is obtained by suction filtration; the crude product is redissolved in tetrahydrofuran, and then anhydrous ethanol is added for re-precipitation, and suction filtration is performed. After repeating this process three times, vacuum drying is performed to obtain the product PDSDA, whose chemical formula is shown in formula (1).

[0031]

[0032] The Schlenk flask was dehydrated and deoxygenated. First, 58 mmol of borane dimethyl sulfide complex and 174 mmol of methylvinyldichlorosilane were injected into a 250 mL Schlenk reaction flask under ice bath conditions, and then reacted at room temperature for 48 hours to obtain tris(dichlorosilylethyl)borane monomer; then 58 mmol of dichloromethylsilane and 324.8 mmol of hexamethyldisilazane were added, and the reaction system was heated in an oil bath. After reacting at 180°C for 2 hours, a transparent viscous liquid was obtained as a hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds (hb-PBSZ), and its chemical formula is shown in formula (2).

[0033]

[0034] The prepared hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds and the prepared PDSDA are completely dissolved in anhydrous tetrahydrofuran in proportion, wherein the mass ratio of the hyperbranched polyborosilazane precursor to PDSDA is 1:0, 20:1, 10:1, and 5:1, respectively. After stirring evenly, a small amount of platinum (0)-1,3-diethylene-1,1,3,3-tetramethyldisiloxane is added as a catalyst, and the temperature is raised to 45°C in an oil bath to react overnight. After the reaction is completed, anhydrous THF is removed by a cold trap device to obtain a black viscous substance, i.e., a PDSDA cross-linked hyperbranched polyborosilazane precursor. The material is transferred to a porcelain boat, thermally cross-linked at 400°C, and then ground into powder using a planetary ball mill. Finally, the powders were pressed into green bodies and pyrolyzed at 1400 °C in a high-temperature tube furnace to obtain ceramic products, which were named hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1, and hb-PBSZ@PDSDA-5:1, respectively.

[0035] Example 2

[0036] This example provides a characterization experiment of hb-PBSZ@PDSDA.

[0037] The PDSDA, hb-PBSZ, hb-PBSZ@PDSDA-20:1 precursor, hb-PBSZ@PDSDA-10:1 precursor and hb-PBSZ@PDSDA-5:1 precursor in Example 1 were measured by Fourier transform infrared spectroscopy, and the following results were obtained: Figure 1 Results shown.

[0038] The hydrogen element nuclear magnetic resonance spectrum and carbon element nuclear magnetic resonance spectrum of the deuterated chloroform solvent of PDSDA in Example 1 are as follows: Figure 2 and Figure 3 shown.

[0039] The hb-PBSZ@PDSDA-10:1 prepared in Example 1 was subjected to electron microscopy scanning and transmission electron microscopy energy spectrum analysis, and the following results were obtained: Figure 4 Results shown.

[0040] XRD analysis was performed on hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 prepared in Example 1, respectively, and the results were as follows: Figure 5 Results shown.

[0041] Raman spectroscopy analysis was performed on hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 prepared in Example 1, respectively, and the following results were obtained: Figure 6 Results shown.

[0042] The reflection coefficient curves of hb-PBSZ@PDSDA-1:0, hb-PBSZ@PDSDA-20:1, hb-PBSZ@PDSDA-10:1 and hb-PBSZ@PDSDA-5:1 prepared in Example 1 were analyzed respectively, and the results were as follows: Figure 7 Results shown.

[0043] Depend on Figure 1 to Figure 3 It can be seen that the present invention successfully prepared PDSDA, and as the content of PDSDA increased, the silicon-hydrogen bond in the infrared spectrum gradually weakened, while the carbon-carbon triple bond gradually strengthened, which indicated that the cross-linking reaction between hb-PBSZ and PDSDA was successful.

[0044] Depend on Figures 4 to 7 It can be seen that the addition of PDSDA helps to form nanofibers and silicon carbide nanocrystals in ceramic absorbing materials. With the increase of PDSDA addition, the diffraction peak of SiC is also enhanced, and the ID / IG value is reduced, indicating that PDSDA can improve the crystallinity and ordered carbon ratio of silicon carbide inside the pyrolysis conversion ceramic. By adjusting the ratio of the two materials, when the mass ratio of hyperbranched polyborosilazane to PDSDA is 10:1, the SiBCN ceramics obtained by pyrolysis at 1400℃ show excellent electromagnetic wave absorption performance in the X-band, with a minimum reflection coefficient of -50.11dB and an effective absorption bandwidth of 2.21GHz. In summary, hb-PBSZ@PDSDA ceramics, as a new type of electromagnetic wave absorbing material, have good application potential for electromagnetic wave absorption.

[0045] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0046] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing polymer-converted microwave-absorbing ceramics, characterized in that: The following steps are involved: The hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds and the poly(diacetylene)dimethylsilane containing alkyne groups are uniformly dissolved in anhydrous tetrahydrofuran at a mass ratio of 5 to 20:1, a catalyst platinum (0)-1,3-diethene-1,1,3,3-tetramethyldisiloxane is added, and the reaction is carried out overnight at a temperature of 45 to 60° C., and then the anhydrous tetrahydrofuran is removed to obtain a polymer precursor; The polymer precursor is thermally cross-linked at 400° C., ground into powder, pressed into an embryonic body, and pyrolyzed at 1400° C. to obtain the polymer-converted microwave-absorbing ceramic.

2. The preparation method according to claim 1, characterized in that: The preparation of the hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds comprises the following steps: Under ice bath conditions, borane dimethyl sulfide complex and methylvinyl dichlorosilane are mixed and added into a reaction container, and then reacted at room temperature to obtain tris(dichlorosilylethyl)borane monomer; Dichloromethylsilane and hexamethyldisilazane are added to the tri(dichlorosilylethyl)borane monomer, and the temperature is raised to 180° C. for reaction for 2 to 4 hours to obtain the hyperbranched polyborosilazane precursor containing silicon-hydrogen bonds.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the borane dimethyl sulfide complex, the methylvinyl dichlorosilane, the dichloromethylsilane and the hexamethyldisilazane is 1:3:1:5.6; And / or, the reaction is carried out at room temperature for 48 hours.

4. The preparation method according to claim 1, characterized in that: The preparation of the poly(diacetylene)dimethylsilane containing alkynyl groups comprises the following steps: n-Butyl lithium and hexachloro-1,3-butadiene are added to anhydrous tetrahydrofuran at a temperature of -78°C under oxygen-free conditions, and stirred for reaction; Slowly add dichlorodimethylsilane and keep reacting; A capping agent is added and a purification treatment is performed to obtain the alkynyl-containing poly(diacetylene)dimethylsilane.

5. The preparation method according to claim 4, characterized in that: The purification process comprises the steps of: After removing excess tetrahydrofuran in the reaction system by rotary evaporation, the reaction system was added dropwise into anhydrous methanol solution for precipitation, and filtered to obtain a crude product; The crude product is redissolved in tetrahydrofuran, anhydrous methanol is added for re-precipitation, and suction filtration is performed. This step is repeated 1 to 3 times and then vacuum dried to obtain the alkynyl-containing poly(diacetylene)dimethylsilane.

6. The preparation method according to claim 4, characterized in that: The molar ratio of the n-butyl lithium, the hexachloro-1,3-butadiene and the dichlorodimethylsilane is 4:1:1; And / or, the stirring reaction time is 6 hours; And / or, the reaction is maintained for 12 hours.

7. The polymer-converted microwave-absorbing ceramic prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the polymer-converted microwave-absorbing ceramics according to claim 7 in the field of aerospace.

Citation Information

Patent Citations

  • Polymer precursor converted Si / C lithium ion battery anode material and preparation method thereof

    CN108807894A

  • Cobalt-containing polymer converted ceramic-based wave-absorbing material and preparation method thereof

    CN109336608A

  • Liquid curable boron-containing polycarbosilane and preparation method thereof

    CN110698678A

  • Benzene ring-containing hyperbranched polyborosilazane converted amorphous SiBCN wave-absorbing ceramic and preparation method thereof

    CN117024144A

  • Process for SiBCN based preceramic polymers and products derivable therefrom

    US20050026769A1